Health education for seniors: An analysis in light of paulo freire's perspective - Bezerra, Italla Maria Pinheiro; Alves, Sabrina Alaide Amorim; De Fátima Antero Sousa Machado, Maria; Zioni, Fabíola; De Lima Antão, Jennifer Yohanna Ferreira; Martins, Ana Aline Andrade; Arrais, Teresa Maria Siqueira Nascimento; Dos Santos, Shayane Bezerra; De Araujo, Aretha Feitosa; Batista, Hermes Melo Teixeira; Valenti, Vitor Engracia [UNESP]; De Abreu, Luiz Carlos (Springer Nature, 2015)
Background: The ageing population is one of the hardest challenges for current public health. However, for proper attention to the elders, the development of reachable social and health policies consistent with the real needs of this population is essential. Thus, this research aimed to analyse the perceptions of nurses about health education for the elderly, drawing upon the conceptions of Paulo Freire. Method: This descriptive study utilised a qualitative approach conducted in the city of Juazeiro do Norte, Ceará, Brazil within the Unidades de Saúde da Família - USF (Family Health Units). Eighteen nurses participated in this study. A semi-structured interview was used for gathering data that was analysed according to content. The analysis of the obtained data began with the conception by Paulo Freire and from some relevant articles related to the topic. Results: Considering the concept of health as a tool to develop people, in this sense some professionals associated health education as being focused on knowledge exchange, behaviour changes, and decision making in health, matching the Freirean ideology of questionable methodology. However, some professionals had a different understanding of health education, focusing on the concept of health, grounded in the absence of a disease, thus characterising a learning bank methodology as they resorted to vertical transmission of knowledge. However, the educational actions performed by those professionals envisioning healthy ageing were directed from the identification of prevalent diseases within the community. Conclusion: Health education is the instrument that enables change in behaviour and decision-making in health care for the users, but it should be planned in an ongoing manner, considering the needs of the population, using methodologies that promote dialogue -an essential element for establishing the necessary link for conducting practical aspects given the perspective of health promotion.
Keywords: Health education; Health promotion; Senior's health